The future of competition and transformation in the global energy market between primary and renewable energy and its repercussions on Iraq - Salem Abdullah*, Hossam; Muhammad Musahib, Jassim (Journal of Economics and Administrative Sciences, 2024)
Oil is considered important and dominant part in the world of energy, especially industrialized and emerging countries, in terms of solidity and production, and it is difficult to dispense with it, especially in the transportation sector. Oil and gas played an important role in pushing the economic movement forward, throughout history, and despite its importance, it is considered largest part of environmental pollutant, most developed countries have begun to search for renewable energy of various types for security, economic, and environmental reasons, despite its high cost compared to fossil fuels.The aim of the research was to identify global expectations for renewable and non-renewable energy sources, and also to identify the repercussions of renewable energy sources on traditional ones, including Iraq, which depends entirely on oil. The study proved through the hypothesis that the role of oil will not decrease in the global energy balance for the coming decades despite the pressures. "The economic, environmental and renewable energy competition is directed towards the depleted resource for that the biggest role will be for gas as well."The research reached several results: “Oil will not be depleted tomorrow,” despite the pressures towards this depleted resource, especially this problem facing the producing countries, and Iraq is part of these countries. Accordingly, Iraq, as a producer of oil and gas, must take practical steps to reduce dependence on oil and move towards alternatives and develop them. By investing in its oil industry and developing it to promote renewable energy that is complementary in the short term and an alternative in the long term, that is, searching for environmentally friendly sources to reduce the phenomenon of pollution, taking into account that the world will abandon fossil fuels in the future, according to Hubbert’s theory, or alternative sources must be replaced Protecting its economy, diversifying its sources, legislating laws, increasing investment, and exploiting its geographical location, which enjoys a comparative advantage, in exploiting renewable energy.Paper type : classification/research paper